Carbonization of excess sewage sludge by using super-heated water vapor to make fuel - Haridan, N. A.; Yoshida, H.; Mohd Salleh, Mohamad Amran; Siajam, Shamsul Izhar (Centre for Environmental Sustainability and Water Security (IPASA), Universiti Teknologi Malaysia, 2019)
Excess sewage sludge was converted to carbonized material using superheated water vapor for use as fuel. The superheated water vapor carbonized the sewage sludge using a bench-scale rotary kiln setup at temperatures between 200°C to 500°C and reaction time of 60 min. The treatment temperature was lower and more rapid than that using N2, CO2, and air. The yield of carbonization decreased when the temperature of carbonization increased. SEM images revealed that the macroscopic structure of carbonized materials strongly depended on the original compositions. The CHNS elemental analyzer and bomb calorimeter were used to measure the heating value of the carbonized products. The heating value of the carbonized material was higher after carbonization. Thus, this study has shown that instead of landfill, excess sewage sludge can be utilized using superheated water vapor for conversion to fuel.